Why do offenders tape their crimes?: crime and punishment in the age of the selfie - Sandberg, Sveinung (The British journal of criminology, 2017)
New technologies have changed the way we produce and relate to images. Three socio-cultural trends and associated offender motivations stand out when understanding why offenders record their crimes. First, some pictures and films are inspired by the rise of amateur and rape pornography and recorded to produce and enjoy such images. Second, recordings are done to further humiliate the victim in a new online culture of humiliation. Third, as part of a new snapshot culture, pictures and films are recorded on impulse when something extraordinary is happening. Visual criminology has focused on analysis of pictures and films as an end product. We take visual criminology beyond images and explore how these are produced as an integral part of criminal activities.